Personality Counselor Perspective Buya Hamka (Study Of Interpretation Of Al-Azhar Verses Advice) - Syariful Syariful (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2019)
Abstract - Talking about the counselor's problem is inseparable from his duty to bring his client to life that is blessed by Allah SWT, and the counselor is able to realize the lifestyle in words, behavior, and mood, so that what the counselor gives to the client provides guidance for the counselor at the same time also become a good practicing in the teachings of Islam. Therefore, it is very important for the counselor to be kind and noble in accordance with what is taught by Islam in the Qur'an and hadith. Hamka as the interpreter of the Qur'an has explained the character and ethics of the counselor. Studying a meaning in the Qur'an certainly requires knowledge and knowledge, and all of that is inseparable from the interpretation of several scholars through the existing interpretive books, one of which examines Hamka's thoughts on the verses that contain the words of advice and irsyad in Tafseer Al-Azhar . Islamic guidance and counseling according to Hamka is a teaching process for someone (client) who does not know or who needs help in a gentle and sincere way to enforce amar ma'ruf and nahi munkar. The character of the counselor according to Hamka in the verses of advice and irsyad, namely: Patient, generous and wise, intelligent, not despairing, not arrogant, humble, compassion and empathy. Whereas counselor ethics according to Hamka in advice verses and irsyad, namely: Openness, religion, amar ma'ruf nahi munkar, and enthusiasm.Keywords - Advice and Irshad, Counselor Personality, Counselor